Peningkatan Hasil Belajar melalui Model Pembelajaran Snowball Throwing pada Pelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar - Soni Jabar Nugroho (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This research has purpose to improve of study result through Snowball Throwing learning model lesson content social studies theme 1 sub theme 2 and 3 in grade V-A SDN Timbulharjo Sewon Bantul. This research is action classroom research and research desain using Kemmis and Mc. Taggart model. Subject in this research were 30 students in grade V-A SDN Timbulharjo. Object in this research were improving study result of students. Instruments used in this research were observation sheet and test. The data obtained were analyzed by descriptive quantitative. The result of this research are improve of study result through Snowball Throwing learning model lesson content social studies theme 1 sub theme 2 and 3 in grade V-A SDN Timbulharjo, that is 61,83 achievment complete of sudent 46,66% in first cycle to 77,33 achievment complete of sudent 90% in second cycle.